Construction of an OVA as a mediating strategy to strengthen the sexual education of 7A students of the Institución Educativa Juan XXIII Mercaderes Cauca - Montenegro Velasco , Diana Lubeida; Arboleda Urrutia, José Julián; Chanchí Golondrino, Gabriel Elías; Velarde Bedregal, Héctor Raúl (I+ T+ C- Research, Technology and Science, 2019)
n this research work was carried out the process of implementing an OVA to manage a pedagogical strategy and strengthen the development of the subject of sexual education of students of 7th grade of the educational institution Juan XXIII of the Municipality of Mercaderes Cauca, with students between 11 and 14 years. The implementation of an OVA as a mediator between knowledge and students to support the development of competencies in education for sexuality. In order to strengthen them, ICT-mediated activities were developed through the LMS Moodle, from which the observation of the incidence of LMS in educational contexts and the levels of understanding reached by students from their interaction with the resources put at their disposal, carrying out the stages of teaching for understanding.